The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018 15th International Bhurban Conference on Applied Sciences and Technology (IBCAST) 2018
DOI: 10.1109/ibcast.2018.8312239
|View full text |Cite
|
Sign up to set email alerts
|

Super twisting control algorithm for blood glucose regulation in type 1 diabetes patients

Abstract: This is an increasing belief that consequences due to hyperglycemia can be mitigated using a close loop control system. This paper investigates a robust non-linear control approach based on sliding mode control (SMC) algorithm for type 1 diabetes patients. Bergman's minimal model have been used to analyse the behaviour of glucose and insulin dynamics in blood plasma inside human body. Control law based on super twisting SMC algorithm is formulated and simulated. Results demonstrated the performance and effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…where ∇ T φ i (ξ ) ∈ 3 represents the gradient of φ i (ξ ) with respect to ξ . Substituting (28) in (29), the following expression is obtained as…”
Section: Gain-scheduled Luenberger Observer (Gslo)mentioning
confidence: 99%
See 1 more Smart Citation
“…where ∇ T φ i (ξ ) ∈ 3 represents the gradient of φ i (ξ ) with respect to ξ . Substituting (28) in (29), the following expression is obtained as…”
Section: Gain-scheduled Luenberger Observer (Gslo)mentioning
confidence: 99%
“…However, the stability of internal dynamics was not confirmed. Conventional and Super twisting-based SMC algorithms are employed for plasma glucose regulation in T1D patients [7], [29]. However, the manipulated input remains out of the feasibility bound.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews on current and emergent control strategies for robotic manipulators are reported in [81]- [83]. Since the last three decades, industrial processes have been classically controlled based on linear control laws [84]. Proportional Integral Derivative (PID) implementation of AUTAREP is reported in [85] while Linear Quadratic Regulator is presented in [86].…”
Section: B Controlmentioning
confidence: 99%
“…There are several previous studies regarding healthcare robotics. As implemented in the Polyclinic of Modena (Italy) [6], Humanoid companion robot for patients [7], assistive robot [8]- [11], end-effector wheeled robotic arm [12], automation and control system in medical sector [13]- [15], and also a robot with a rehabilitation function and motion assitance [16]- [23]. In addition, there are also robots with slightly different goals, namely to disinfect the environment using UV light which can also be applied for healthcare purposes [24].…”
Section: Introductionmentioning
confidence: 99%